Edukasi Pencegahan Narkoba dan Judi Online di Desa Huta Lombang Kecamatan Puncak Sorik Marapi - Redi Hendika; Reza Fansyuri Rangkuti; Ahmad Sapani; Diah Lestari; Sangkot Anisa; Najwa Ahsanah; Riadoh Riadoh; Nur Sakiyah; Salmiah Indriyani; Khoirun Nisah; Muhlisah Lubis (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The issue of drug abuse and the rise of online gambling have become serious threats that significantly affect the social, economic, and health aspects of society. Huta Lombang Village, located in Puncak Sorik Marapi District, is one of the areas vulnerable to these problems, particularly among the younger generation. This educational program aims to provide awareness to the community regarding the dangers of drugs and online gambling, as well as to instill the importance of early prevention. The methods applied include counseling sessions, interactive discussions, and the use of educational media. The results indicate an increase in community knowledge about the negative impacts of drugs and online gambling, along with the emergence of a shared commitment to create a healthy, productive, and drug-free village environment. Such educational initiatives are expected to serve as strategic measures to protect communities from the growing threats of drugs and online gambling.